Diet-Intestinal Microbiota Axis in Osteoarthritis: A Possible Role - Yusheng Li; Wei Luo; Zhenhan Deng; Guanghua Lei (Mediators of Inflammation)
Intestinal microbiota is highly involved in host physiology and pathology through activity of the microbiome and its metabolic products. Osteoarthritis (OA) is a common form of arthritis characterized by articular cartilage destruction and osteophyte formation. Although various person-level risk factors, such as age, sex, and obesity, have been proposed for the pathogenesis of OA, the underlying links between these person-level factors and OA are still enigmatic. Based on the current understanding in the crosstalk between intestinal microbiota and these risk factors, intestinal microbiota could be considered as a major hidden risk factor that provides a unifying mechanism to explain the involvement of these person-level risk factors in OA.